Role of Reduced Exogenous Organic Compounds in the Physiology of the Blue-Green Bacteria (Algae): Photoheterotrophic Growth of an “Autotrophic” Blue-Green Bacterium - Ingram, L. O. (1973)
The unicellular blue-green bacterium Agmenellum quadruplicatum strain BG-1 was found to be capable of rapid photoheterotrophic growth but unable to grow in the dark on a variety of reduced organic substrates. The generation time on glycerol was 12 h, and on CO(2), 3 h. Glycerol carbon was converted into cellular carbon with a very high efficiency. This high efficiency of carbon conversion, the action spectrum for growth on glycerol, cell pigmentation, gas exchange measurements, and immediate ability of photoheterotrophically grown cells to evolve O(2) (upon the addition of CO(2)) suggest the involvement of both photosystems I and II of photosynthesis during photoheterotrophic growth.